Impact analysis of development cooperation is feasible - Susanne Neubert (Deutsches Institut für Entwicklungspolitik (DIE), 2004)
With the new “orientation towards impacts” from the planning to the evaluation of development projects, development cooperation has set itself the goal of becoming more effective and more transparent. This has made impact analysis highly topical. Besides accountability, the goal pursued with them is to learn from the results of development policy interventions, i.e. to formulate best practices where possible or to correct mistakes where necessary.In the wake of the programme and budget orientation of development cooperation, development policy is tending to be implemented at an ever more highly aggregated level. With development cooperation geared to the Millennium Development Goals (MDGs), however, the hoped-for impacts are also being increasingly sought at the level of the people, i.e. at micro level. With the interventions occurring at macro level and the impacts at micro level, the attribution gap between certain interventions and impacts is becoming even wider.The scepticism of the professional world about the feasibility of impact analysis is therefore tending to grow. With the increasing orientation of development cooperation towards programme and budget aid, the accurate definition of donor contributions to the achievement of certain goals may wane in significance, but it will continue to be important to determine what interventions have what impact and why. Consequently, impact analyses and the associated difficulties will still be an issue when the expected change of direction in development cooperation has been completed.This paper argues that impact analysis is feasible today and will be feasible in the future. To take the conceptual debate a step further, four challenging propositions are put forward and explained after the subject has been introduced. An approach to coping with the methodological difficulties is also presented.
Keywords: 330